Ash in the belly: India's unfinished battle against hunger - "Mander, Harsh" (New Delhi, 2012)
This book tell about is a penetrating account of men, women and children living with hunger, illuminated by their courage in trying to cope and survive. It is simultaneously an investigation into the political economy of hunger, whereby one in every two children is malnourished, despite the creation of wealth and economic growth.
Keywords: Hunger